2019
DOI: 10.1016/j.electacta.2019.135105
|View full text |Cite
|
Sign up to set email alerts
|

Dual microelectrodes decorated with nanotip arrays: Fabrication, characterization and spectroelectrochemical sensing

Abstract: Gold microelectrodes decorated with nanotips were developed for spectroelectrochemical experiments. These new dual probes were fabricated by combining fabrication processes of scanning near-field optical microscopy with photolithography. A nanotip array was produced at the surface of a coherent optical fiber bundle by a wet chemical etching step. The resulting nanostructured surface was sputter-coated with a thin gold layer. This gold film conferred plasmonic properties to the sharp nanotips and served as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…This requirement excludes screen printing. MEAs were prepared by photolithography following the procedures described by Bombail et al 43 and also Lambie et al 44 We did not attempt to miniaturize the resonators themselves as reported by Michalzik et al 45 or to produce arrays of sensors as reported by Rabe et al 46 The Braunschweig group scaled the resonators down in size from 38.1 mm to 3 mm and constructed an 8 × 8 array of resonators on a single quartz wafer using reactive ion etching. The methods chosen here are much simpler.…”
Section: Preparation Of the Measmentioning
confidence: 99%
See 1 more Smart Citation
“…This requirement excludes screen printing. MEAs were prepared by photolithography following the procedures described by Bombail et al 43 and also Lambie et al 44 We did not attempt to miniaturize the resonators themselves as reported by Michalzik et al 45 or to produce arrays of sensors as reported by Rabe et al 46 The Braunschweig group scaled the resonators down in size from 38.1 mm to 3 mm and constructed an 8 × 8 array of resonators on a single quartz wafer using reactive ion etching. The methods chosen here are much simpler.…”
Section: Preparation Of the Measmentioning
confidence: 99%
“…This requirement excludes screen printing. MEAs were prepared by photolithography following the procedures described by Bombail et al 43 and also Lambie et al 44…”
Section: Background: Microelectrode Arraysmentioning
confidence: 99%
“…optical and electrochemical. The current protocol derives from a previously reported one [50], aimed at designing gold microelectrodes possessing arrays of nanotips on their surface, and their use for spectro-electrochemical characterization of surfaces (physical, biological) by e.g. combined SECM (Scanning Electrochemical Microscopy) [51] and SERS (Surface Enhanced Raman Spectroscopy).…”
Section: Optoelectrode Fabricationmentioning
confidence: 99%
“…Fabrication of electrochemical sensors that take advantage of optical properties has been explored recently in literature, known as spectroelectrochemical sensors. 84,85 This combined approach is well suited for NPG, which possesses both of these properties, making it a strong candidate for this technique going forward which may lead to improved selectivity and sensitivity.…”
Section: Npg Based Optical Sensorsmentioning
confidence: 99%